MicroRNA-939 amplifies Staphylococcus aureus-induced matrix metalloproteinase expression in atopic dermatitis - Wang, Jiating; Huang, Yejing; Wu, Xinfeng; Li, Dongqing (Frontiers in Immunology, 2024)
Background Atopic dermatitis (AD) is a common chronic inflammatory skin diseases that seriously affects life quality of the patients. Staphylococcus aureus (S. aureus) colonization on the skin plays an important role in the pathogenesis of AD; however, the mechanism of how it modulates skin immunity to exacerbate AD remains unclear. MicroRNAs are short non-coding RNAs that act as post-transcriptional regulators of genes. They are involved in the pathogenesis of various inflammatory skin diseases. Methods In this study, we established miRNA expression profiles for keratinocytes stimulated with heat-killed S. aureus (HKSA). The expression of miR-939 in atopic dermatitis patients was analyzed by fluorescence in situ hybridization (FISH). miR-939 mimic was transfected to human primary keratinocyte to investigate its impact on the expression of matrix metalloproteinase genes (MMPs) in vitro. Subsequently, miR-939, along with Polyplus transfection reagent, was administered to MC903-induced atopic dermatitis skin to assess its function in vivo. Results MiR-939 was highly upregulated in HKSA-stimulated keratinocytes and AD lesions. In vitro studies revealed that miR-939 increased the expression of matrix metalloproteinase genes, including MMP1, MMP3, and MMP9, as well as the cell adhesion molecule ICAM1 in human primary keratinocytes. In vivo studies indicated that miR-939 increased the expression of matrix metalloproteinases to promote the colonization of S. aureus and exacerbated S. aureus-induced AD-like skin inflammation. Conclusions Our work reveals miR-939 is an important regulator of skin inflammation in AD that could be used as a potential therapeutic target for AD.